2011
DOI: 10.1007/s11192-011-0570-z
|View full text |Cite
|
Sign up to set email alerts
|

The success-index: an alternative approach to the h-index for evaluating an individual’s research output

Abstract: Among the most recent bibliometric indicators for normalizing the differences among fields of science in terms of citation behaviour, Kosmulski (Journal of Informetrics 5(3):481-485, 2011) proposed the NSP (Number of Successful Paper) index. According to the authors, NSP deserves much attention for its great simplicity and immediate meaning-equivalent to those of the h-indexwhile it has the disadvantage of being prone to manipulation and not very efficient in terms of statistical significance. In the first par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 34 publications
0
39
0
1
Order By: Relevance
“…Estimating the citation propensity by using the distribution of (i) the number of references given or (ii) the citations obtained by the publications of the reference sample. We remark that the condition that the average number of references given should be equal to the average number of citations obtained is valid only within relatively closed information fields (Vinkler 2004;Franceschini et al 2012a). 3.…”
Section: Brief Remarks On the Success-indexmentioning
confidence: 97%
See 3 more Smart Citations
“…Estimating the citation propensity by using the distribution of (i) the number of references given or (ii) the citations obtained by the publications of the reference sample. We remark that the condition that the average number of references given should be equal to the average number of citations obtained is valid only within relatively closed information fields (Vinkler 2004;Franceschini et al 2012a). 3.…”
Section: Brief Remarks On the Success-indexmentioning
confidence: 97%
“…According to the formal definition of the success-index (Franceschini et al 2012a), a score is associated to each (i-th) of the (P) publications of interest:…”
Section: Brief Remarks On the Success-indexmentioning
confidence: 99%
See 2 more Smart Citations
“…Other authors have suggested several other h-type indices including the g-index [7], H (2) -index [8], success index [9], A-and AR-indices [10] and R-index [11]. Additional studies have proposed new h-type indices or related them to research evaluation methods [12][13][14][15][16].…”
Section: Introduction and Objectivesmentioning
confidence: 99%